Chile : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper examines a number of potential factors that may have influenced the short-term behavior of the exchange rate between the Chilean peso and the U.S. dollar during the period of floating exchange rate, including the possible impact of developments in Argentina during 2001. The paper investigates whether copper prices can be successfully forecasted over medium-term horizons, emphasizing the properties of copper prices most relevant in the Chilean context, including for fiscal policymaking. The paper also provides a snapshot of the Chilean banking and corporate sectors.